2013
DOI: 10.1007/s00167-013-2656-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of different suture materials for arthroscopic transtibial pull-out repair of posterior meniscus root tears

Abstract: None of the evaluated suture materials provided clearly superior properties over the others during both cyclic loading and load-to-failure testing. Based on the results of this study, FiberWire™ may be the preferred suture material for transtibial pull-out repair of posterior meniscus root tears because of comparably low displacement during cyclic loading and high values for maximum load and stiffness. In the clinical setting, FiberWire™ may improve healing rates and avoid progressive extrusion of the meniscus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 57 publications
4
84
0
Order By: Relevance
“…Kopf et al 18 were also the first to compare native root strength versus repair strength after various suture fixation techniques, and they found that none of their tested suture fixation methods (ie, 2 simple sutures, modified Kessler stitch, or loop stitch) adequately restored the strength of the native meniscal roots. Two recent studies by Feucht et al 6,8 corroborate these findings with similar results in a porcine model using different suture fixation techniques.…”
Section: Discussionsupporting
confidence: 62%
“…Kopf et al 18 were also the first to compare native root strength versus repair strength after various suture fixation techniques, and they found that none of their tested suture fixation methods (ie, 2 simple sutures, modified Kessler stitch, or loop stitch) adequately restored the strength of the native meniscal roots. Two recent studies by Feucht et al 6,8 corroborate these findings with similar results in a porcine model using different suture fixation techniques.…”
Section: Discussionsupporting
confidence: 62%
“…24 Besides biological factors, such as tissue degeneration and blood supply, the biomechanical properties of the repair technique may play an important role during the healing process. 22,23 All but 1 study included in this systematic review used simple stitches for root repair, whereas only 1 group used a modified Mason-Allen technique. 28 In a biomechanical study, Feucht et al 22 evaluated the biomechanical properties of 4 different suture techniques for ATPR and found that the modified Mason-Allen technique provided the best biomechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Stiffness (as defined by Feucht et al 22 ) was determined. Since a constant stiffness value was considered too limited due to the non-linear load-displacement response, displacements at representative subcritical loads of 50, 75 and 90 N were calculated to characterize the deformation under load of the complex.…”
Section: Biomechanical Testingmentioning
confidence: 99%